Transformacja Sojuszu Lewicy Demokratycznej - od koalicji wyborczej do partii politycznej - Przemysław Woliński (Świat Idei i Polityki, 2002)
The subject of this paper is transformation of the Democratic Left Alliance from an election organism focusing a wide range of post-communistic groups into an organizationally uniform political party. The election coalition could start to exist as a result of transformations in the political system of the state after the breakthrough in 1989 when the political life was submitted to plurálisadon. The paper presents the main actors of the election coalition of the Democratic Left Alliance: the parties and political and social groups with a special dominant role of the Social Democratic Party of Poland, and the relations between them. Besides, it presents the development of the coalition and its election and parliamentary activities. There are also presented the ideas of a new political formation with the process of its foundation. The decade of the nineties is characteristic for foundation, development and transformation of the Democratic Left Alliance as well as for working out a partnership with a left party of a different origin, i.e. the Union of Labour, which enables us to define these years as a stage of the Social Democratic Camp formation in the Republic of Poland. It was the stage of bringing closer together and uniting different subjects of the left within its main stream focused around the Social Democratic Party of Poland, and then its internal institutionalization. Preservation of a wide formula of the Left consolidation still made its ideological-policy identification difficult, which is, as it can be predicted, a challenge for the new decade.